Strategi Manajemen Guru terhadap Motivasi Siswa dalam Penguasaan Bahasa Asing di MI Muhammadiyah Ajibarang - Wibowo, Rochmat Cahyo; Yusuf, Enjang Burhanudin (Lembaga Yasin AlSys, 2025)
This article discusses teacher management strategies for enhancing students’ motivation in mastering foreign languages, particularly English, at MI Muhammadiyah Ajibarang, Banyumas. The teaching and learning process is understood as an interaction between teachers and students aimed at achieving optimal learning outcomes. In this context, student motivation is a key factor influencing learning success, as mental drives such as desire and aspiration can direct learning behavior. The objective of this study is to identify the instructional management strategies employed by teachers to foster student learning motivation, as well as their impact on foreign language acquisition. A qualitative method was used, with data collected through interviews and classroom observations. The findings reveal that teachers apply a range of management strategies, including the use of audio-visual media and the implementation of interactive learning methods such as Project-Based Learning. Observations indicated that approximately 80% of students actively participated in the learning process, contributing positively to increased motivation and English language proficiency. Instructional approaches that are relevant to students’ real-life experiences were also found to enhance their learning interest. The study concludes that innovative and contextual management strategies can create a conducive and engaging learning environment, thereby encouraging students to be more motivated in learning foreign languages. The implication is that these findings offer practical guidance for teachers seeking to improve the quality of language instruction at the primary school level.